Research on Reservoir Numerical Simulation with Consideration of Time-dependent Physical Properties. Issue 4 (March 2021) - Zhao, Pingqi; Ni, Tianlu; He, Shumei; Huang, Fang; Liang, Xiao; Zhang, Zhipeng; Wei, Pengpeng; Yu, Gaoming
Abstract: Fine reservoir description is an important prerequisite to ensure the scientific and efficient development of oilfields. Reservoir numerical simulation is an important tool for efficient development. The accuracy of reservoir description determines the reliability of numerical simulation results. After long-term water injection development, the physical properties of the reservoir have undergone great changes. How to identify the time-dependent law of reservoir physical properties and finely characterize them during numerical simulation has been the focus and research difficulty in this field in recent years. This paper combines the results of previous studies on the changes of reservoir physical properties in the later stage of water drive development in Area A with numerical simulation methods. Predecessors realized time-dependent numerical simulation methods include staged numerical simulation and self-developed numerical simulation programs. Although the above two types of methods can achieve the purpose of realizing time-dependent numerical simulation, they all have certain defects. The segmented simulation method requires multiple modeling, heavy workload, multiple manual operations, and poor continuity and non-directional calculation results. Although the self-developed numerical simulation program calculation results can have better continuity and directionality, but this requires a lot of manpower and material resources to carry out the research. The research and development cost is high, the cycle is long, and the simulation accuracy and speed are difficult to reach the level of commercial numerical simulation software in the short term. Based on the above analysis, this paper has developed a simulation program TD-SIM (Time Dependent Simulation) that combines the commercial numerical simulation software ECLIPSE and can realize the time-dependent function of the reservoir permeability field. This program has convenient use and low cost. At the same time, it is necessary to take into account faster simulation speed, higher simulation accuracy, and better continuity and directionality of the simulation results.